Mixed Conductive, Injectable, and Fluorescent Supramolecular Eutectogel Composites - Criado-Gonzalez, Miryam (2023)
The financial support received from CONICET and ANPCyT (Argentina) is also gratefully acknowledged. M. C.‐G. thanks Emakiker Grant Program of POLYMAT. L. C. T. is grateful to Fundação para a Ciência e a Tecnologia (FCT/MCTES) in Portugal for her research contract under Scientific Employment Stimulus (2020.01555.CEECIND). D. M. thanks “Ayuda RYC2021‐031668‐I financiada por MCIN/AEI/10.13039/501100011033 y por la Unión Europea NextGenerationEU/PRTR”. The authors thank the technical and human support provided by SGIker (UPV/EHU/ERDF, EU). Publisher Copyright: © 2023 The Authors. Angewandte Chemie International Edition published by Wiley-VCH GmbH.